1993
DOI: 10.1111/j.1699-0463.1993.tb00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the cellular fatty acids of methicillin-resistant and -susceptibleStaphylococcus aureus

Abstract: The cellular fatty acid compositions of 26 strains of methicillin‐resistant Staphylococcus aureus (MRSA) and 17 strains of methicillin‐susceptible S. aureus (MSSA) were analyzed by gas‐liquid chromatography. The fatty acid compositions of the two groups were very similar with 16 identified components. The major fatty acids were Ci14 = 0, Ci15 = 0, C18 = 0 and C20 = 0. Among these fatty acids, the percentage of the Ci15 = 0 fatty acid component of MRSA strains (11.4 ± 3.9%) was statistically higher than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There has been some research about the cellular fatty acid compositions of S. aureus (Theodore & Panos ; Asai et al . ). Theodore and Panos reported that pentadecanoic acid (C15:0), heptadecanoic acid (C17:0) and nonadecanoic acid (C19:0) fatty acids were dominant in the plasma membrane of S. aureus (Theodore & Panos ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There has been some research about the cellular fatty acid compositions of S. aureus (Theodore & Panos ; Asai et al . ). Theodore and Panos reported that pentadecanoic acid (C15:0), heptadecanoic acid (C17:0) and nonadecanoic acid (C19:0) fatty acids were dominant in the plasma membrane of S. aureus (Theodore & Panos ).…”
Section: Discussionmentioning
confidence: 97%
“…The study about the cellular fatty acid composition of S. aureus showed that the major fatty acids were myristic acid (C14:0), C15:0, stearic acid (C18:0) and arachidic acid (C20:0) (Asai et al . ). It has been reported that the percentage of the C15:0 fatty acid component of MRSA strains was higher than that of MSSA strains (Asai et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This identification system utilizes the type and amount of cellular fatty acids present in the lysate of an organism. Many species have unique cellular fatty acid chromatographic profiles [9,13]. Relationships between strains of a particular species may be inferred from highly similar cellular fatty acid profiles [7].…”
Section: Chromatographic Analysismentioning
confidence: 99%
“…The fatty acid profiles of LZ-01, LZ-02, LZ-03, LZ-04 and S. aureus type strains ATCC29213 and ATCC25923 [41,42] were presented in supplementary figure 3. The major fatty acids of the strains tested were C 15:0 iso, C 15:0 anteiso, C 16:0 , C 17:0 iso, C 17:0 anteiso and C 18:0 .…”
Section: Phylogenetic Analysis Of Isolated Strainsmentioning
confidence: 99%